Isolation and Identification of Bifidobacterium longum subsp infantis isolated from cow milk and its antibacterial activity - Divya SB; Radhai Sri S; R Ragunathan; Jesteena Johney (The Bioscan, 2025)
Bifidobacteria are common probiotics associated with health-promoting “functional foods” as well as therapeutic, prophylactic and growth supplements for humans. The study was designed to isolate and characterise Bifidobacteria from raw cow milk and to provide a more inclusive report for their probiotic potential. The presumptive isolate was assessed for tolerance to pH and bile salt. Subsequently, probiotic potential and safety evaluation were confirmed through antibacterial activity and antibiotic susceptibility. The most promising strain with remarkable probiotic potential was identified by 16S rRNA gene sequencing as the Bifidobacterium longum subsp infantis strain. The strain showed good tolerance to 0.3% bile salts after 6 hrs of exposure. The growth of Bifidobacterium longum was observed at 4% Nacl with an OD value of 0.684. B.longum showed survivability at pH ranging from 2.0, 5.0 and 7.0 through turbidity of growth confirming the acid tolerance property. In addition, the strain also exhibited antimicrobial activity (agar well diffusion method) towards intestinal pathogens, such as Escherichia coli, Staphylococcus aureus, Bacillus subtilis, and Pseudomonas aeruginosa. The antibiotic susceptibility profile of the isolated strain was tested using the disc diffusion method and found to be resistant to the antibiotics. The findings of this study showed that the Bifidobacteria strain isolated from raw cow milk, a promising probiotic could be used as a dietary adjunct or for the development of new functional foods.